(untitled) (BIBECHANA, 2023)
The fabrication of electric double layer thin film transistors (EDLTFTs) using polymeric electrolyte as gate dielectric on chemically grown polycrystalline ZnO thin film channel has the lower threshold voltage at 0.4 V and the saturation current at 3 µA in the dark. The lower threshold voltage is -1 V and the saturation current is 10 µA in the UV illumination. In the dark and under UV light, the off state ID is 1 nA and 0.3 µA respectively and under gate and UV illumination the on current shows more than 3 times enhancement. This improvement in photocurrent is due to the combined effect of gate and UV illumination. The field effect mobility of the TFT is 0.06 cm2/Vs in the dark and 0.16 cm2/Vs under UV illumination. This increase in mobility under illumination and gate bias is due to the increase in carrier concentration and reduction of charged defects in the channel length.